The Young Marooners on the Florida Coast - Goulding, F. R. (Francis Robert), 1810-1881; Harris, Joel Chandler, 1848-1908 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Young Marooners on the Florida Coast" by F. R. Goulding is a novel written in the mid-19th century. The story revolves around Dr. Gordon and his children, Robert, Mary, and Frank, who embark on an adventurous journey from Charleston to Tampa Bay, Florida. Their journey is filled with learning experiences and challenges that intertwine nature, survival skills, and familial bonds as they prepare for an expedition into the wild. The opening of the narrative introduces the Gordon family and their motivations for traveling to Florida, where Dr. Gordon believes the climate will benefit his ailing wife. As the family boards the brig, they experience the excitement of sailing, where the children, especially Mary and Frank, engage in fishing and interact with the maritime environment. The interactions among the family members reveal their personalities, showcasing Robert's thirst for knowledge, Harold's robust nature, and the close relationships they share. The initial chapters set the tone for a story steeped in adventure, reflection, and practical lessons about life on the coast, indicating that the marooning experience will be both thrilling and educational. (This is an automatically generated summary.)
Release date is 2013-02-10
Produced by Al Haines
Keywords: Islands -- Juvenile fiction; Rescues -- Juvenile fiction; Castaways -- Juvenile fiction; Robinsonades; Survival -- Juvenile fiction; Florida -- Description and travel -- Juvenile fiction; Natural history -- Florida -- Juvenile fiction; Tampa Bay (Fla.) -- Juvenile fiction